Cytodiagnosis of Castleman's disease: A diagnostic challenge - Muktha R Pai; Sushma Hosamane; Nisha J Marla (Wolters Kluwer Medknow Publications, 2016)
Castleman's disease (CD) is an uncommon cause of solitary or multiple lymphadenopathy, which may be a target for fine-needle aspiration (FNA). Because of its rarity and lack of adequate literature available on its cytomorphological findings, the condition is misdiagnosed or missed out during routine FNA reporting. The presence of small lymphocytes and plasma cells with large atypical binucleate follicular dendritic cells resembling Reed-Sternberg cells may raise a suspicion of Hodgkin lymphoma (HL). Here, we report the cytodiagnosis and pitfalls in the diagnosis of CD in three cases. FNA smears were reviewed and pitfalls in the diagnosis analyzed and correlated with histopathological findings.